Long-term results after gastrocnemius-soleus intramuscular aponeurotic recession as a part of multilevel surgery in spastic diplegic cerebral palsy - Dreher, Thomas; Buccoliero, Tanja; Wolf, Sebastian Immanuel; Heitzmann, Daniel; Gantz, Simone; Braatz, Frank; Wenz, Wolfram (The journal of bone & joint surgery. A, American volume, 2012)
Background: Equinus of the foot at the ankle is one of the most common deformities in patients with spastic diplegic cerebral palsy, leading to gait disturbances and secondary deformities. During single-event multilevel surgery, equinus is commonly corrected by calf muscle lengthening, such as gastrocnemius-soleus intramuscular aponeurotic recession. Various studies have described satisfactory short-term results after gastrocnemius-soleus intramuscular aponeurotic recession. However, there is no evidence for maintenance of equinus correction because of the small and heterogeneous case series and short follow-up time previously reported. Methods: The present study provides long-term results after gastrocnemius-soleus intramuscular aponeurotic recession as a part of multilevel surgery for the treatment of equinus in forty-four patients with spastic diplegia who were able to walk (forty-eight legs had lengthening of the gastrocnemius and thirty-four legs had lengthening of the gastrocnemius and soleus). Standardized three-dimensional gait analysis and clinical examination were done preoperatively and at one year, a mean (and standard deviation) of 3 ± 1 years, and a mean of 9 ± 2 years after surgery. Results: Significant improvements in kinematic and kinetic ankle parameters on gait analysis as well as passive dorsiflexion in clinical examination were found one year after surgery. While there was a significant loss of passive dorsiflexion at the time of long-term follow-up, the improvements in gait analysis parameters were maintained. The endurance of gait improvements was accompanied by a persistent increase of dorsiflexor muscle strength without relevant loss of plantar flexor strength. Although it was not significant, there was a tendency for deterioration of gait analysis parameters over the nine years. The analysis of individual patterns showed recurrence of equinus at the ankle in 24% of the legs. Early-onset calcaneal gait was found one year after surgery in seven legs (9%), but without secondary crouch gait, and there was recovery at the time of the long-term follow-up. Late-onset calcaneal gait was seen at the time of long-term follow-up in eight legs (10%), of which four had an accompanying crouch gait. Conclusions: Gastrocnemius-soleus intramuscular aponeurotic recession as a part of multilevel surgery leads to satisfactory correction of mild and moderate equinus deformity in children and adolescents with spastic diplegia without relevant risk for overcorrection and should be preferred over Achilles tendon lengthening to avoid overlengthening. The long-term results in the present study demonstrate that the improvements are long-lasting on average, but individual patients tend to develop recurrence and may need secondary gastrocnemius-soleus intramuscular aponeurotic recession.
Gesehen am 11.12.2018